2021
DOI: 10.1021/acs.est.0c06752
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of α-Pinene Secondary Organic Aerosol Dominated by Moderately Oxidized Molecules

Abstract: Atmospheric secondary organic aerosol (SOA) undergoes chemical and physical changes when exposed to UV radiation, affecting the atmospheric lifetime of the involved molecules. However, these photolytic processes remain poorly constrained. Here, we present a study aimed at characterizing, at a molecular level and in real time, the chemical composition of α-pinene SOA exposed to UV-A light at 50% relative humidity in an atmospheric simulation chamber. Significant SOA mass loss is observed at high loadings (∼100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 49 publications
(97 reference statements)
1
18
1
Order By: Relevance
“…S6. Previous studies have found significant fractions of photo-recalcitrant material when SOA photolysis was performed in the organic particle phase, including for high-NO x toluene SOA (O'Brien and Kroll, 2019;Walhout et al, 2019;Baboomian et al, 2020;Pospisilova et al, 2021), and based on these studies we expect a photorecalcitrant fraction for the SOA studied here. When the photo-recalcitrant fraction was not constrained to zero, the obtained fit estimates a large photo-recalcitrant absorbance fraction (49 ± 5 %).…”
Section: Optical Propertiessupporting
confidence: 66%
“…S6. Previous studies have found significant fractions of photo-recalcitrant material when SOA photolysis was performed in the organic particle phase, including for high-NO x toluene SOA (O'Brien and Kroll, 2019;Walhout et al, 2019;Baboomian et al, 2020;Pospisilova et al, 2021), and based on these studies we expect a photorecalcitrant fraction for the SOA studied here. When the photo-recalcitrant fraction was not constrained to zero, the obtained fit estimates a large photo-recalcitrant absorbance fraction (49 ± 5 %).…”
Section: Optical Propertiessupporting
confidence: 66%
“…It is possible that the SOA production was actually enhanced due to synergy between ozonolysis and photooxidation and then lowered by photolysis, as some studies have suggested that the yield from monoterpene ozonolysis could be reduced in the presence of light. 52,53 However, a recent study suggested that the SOA loss due to photolysis is negligible at low aerosol loadings (∼20 μg m −3 ), 54 and the aerosol loadings in our experiments were even lower (∼10 μg m −3 ). In addition, the effect of photolysis has been observed most clearly in batch-mode experiments where SOA age continuously increased with time, while in continuous-mode experiments, aerosol has a distribution of age.…”
Section: Effect Of Ozonolysis: Formation Of Elvocscontrasting
confidence: 60%
“…This is important because most BrC photobleaching studies to date have been performed on bulk liquid solutions, 56−60 even if the brown carbon was initially formed in suspended aerosol. 59 The optical parameters of BrC from each experiment are compared to the recent atmospheric BrC classification scheme of Saleh et al 71,72 in Figure 5. It can be seen that BrC formed in dark, bulk-phase reactions between carbonyl species and AS (black triangle) does not match atmospheric BrC in absorptivity, expressed as log(MAC 405 ), and on average has a wavelength dependence (expressed as AAE 330−400 ) that is steeper.…”
Section: ■ Results and Discussionmentioning
confidence: 99%